Social determinants of health in teenage girls involved with sexual exploitation on downtown streets late at night - Tanaka, Tsutomu (Nagoya J Med Sci, 2019)
The purpose of this study was to chronicle the experiences of teenage girls who stay downtown late at night and are involved in sexual exploitation, and to clarify characteristics of their social circumstances and social determinants of health: socioeconomic status and educational opportunities. Between November 2009 and June 2013, we spoke with 89 adolescents who were loitering late at night in downtown Nagoya, Japan. We focused our research efforts on a case series of 22 girls who were 14–19 years of age and were involved in sexual exploitation. Semi-structured interviews were performed with the use of a questionnaire on the girls’ sexual and mental health, families, school life, living conditions, and future aspirations. Along with the questionnaires, we analyzed case series interviews with a qualitative approach (narratives-under-analysis by in-depth understanding in context). Nine girls worked in the sex industry, while thirteen were independent sex workers. Our observations included child maltreatment, unstable families, distressing school life, insufficient education, and inappropriate relationships with gangs and similar organizations. Moreover, an illegal sex market was linked with these gang associations. Despite their severe living conditions, most of them hoped to have happy families someday. To provide support to this vulnerable population and support their life aspirations, improvement of public health, social welfare, education, and school health systems should be considered carefully.